On the Cyclicality of Research and Development - Barlevy, Gadi (American Economic Review, 2007)
Economists have recently argued recessions play a useful role in fostering growth. Yet a major source of growth, R&D, is procyclical. This paper argues one reason for procyclical R&D is a dynamic externality inherent in R&D that makes entrepreneurs short-sighted and concentrate their innovation in booms, even when it is optimal to concentrate it in recessions. Additional forces may imply that procyclical R&D is desirable, but equilibrium R&D is likely to be too procyclical, and macroeconomic shocks are likely to have overly persistent effects on output and make growth more costly than in the absence of such shocks.